Extreme Moderates: Understanding Low Levels of Violent Extremism in Bosnia-Herzegovina - Pehlivanovic, Sejla (Journal of Regional Security, 2024)
How can low levels of violent extremism in enabling environments be explained? The conflicted political environment and war history of Bosnia-Herzegovina have allowed extra-institutional groups to challenge formal institutions. Despite this, there have been few violent extremist attacks, and those that have been carried out were small-scale and failed to expose any deep reservoir of violent extremism. What, then, does this deviant case reveal? Utilizing social movement theory and political opportunity structures, the article explores how structural conditions in the Bosnian political and discursive space affect the protest repertoires of extremist movements. Two main arguments are put forward. First, extra-institutional groups must be understood as rational actors with broader claims that exceed the use of violence. Second, distinguishing between radicalization that links to violent extremism and radicalization that aims to initiate societal change through non-violent means can help us better understand the dynamics behind societal change in fragile environments.